2013
DOI: 10.1111/1468-2346.12039
|View full text |Cite
|
Sign up to set email alerts
|

Africa and the rising powers: bargaining for the ‘marginalized many’

Abstract: With abundant resources and growing markets, the African continent is once again at the centre of a new ‘great game of courtship’ between the established and rising powers. However, compared with previous decades, African countries are no longer passive players in international relations. This article explores Africa's recent negotiating behaviour in relation to a selected set of actors that animate the current shifting global economic order: rising powers, established powers and international organizations. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 11 publications
0
29
0
Order By: Relevance
“…15 In general, though, the present authors make the case that only very deep economic and political integration complemented by much more rapid and sustained economic growth in Africa could offset its limited role in shaping global governance.…”
mentioning
confidence: 64%
“…15 In general, though, the present authors make the case that only very deep economic and political integration complemented by much more rapid and sustained economic growth in Africa could offset its limited role in shaping global governance.…”
mentioning
confidence: 64%
“…Environmental regulation invariably constrains land availability; however, research on the benefits of ecosystem services in Durban has revealed that the environmental risk-reducing benefits outweigh the losses from economic growth in 76. Vickers, B (2013), "africa and the rising powers: bargaining for the 'marginalized many '", International Affairs Vol 89, no 3, pages 673-693. 77.…”
Section: Urban Management Implications For Informal Settlementsmentioning
confidence: 99%
“…However, since the turn of the century China has moved towards building and backing new institutions better reflecting its interests ('norm-making'). Examples include financial institutions such as the AIIB and the New Development Bank, security regimes such as the Shanghai Cooperation Organisation and the Conference on Interaction and Confidence-Building in Asia, and 'hub and spoke' regional organisations designed to position Beijing as an alternative partner to other great powers, with one example being the Forum on China-Africa Cooperation (Vickers 2013;Lanteigne 2016: 73-99).…”
Section: Thin Ice: Obstacles To China As An Arctic Actormentioning
confidence: 99%